2014
DOI: 10.1590/0103-5150.027.003.ao10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and physical exercise on balance of healthy young adults

Abstract: Objective To verify the effects of gender and physical activity on postural sway. Method A cross-sectional study was conducted to analyze upright balance of young men and women between the ages of 20-30, both active and sedentary. Study participants were 60 individuals, who were divided into: active women (n = 15), sedentary women (n = 15), active men (n = 15) and sedentary men (n = 15). The International Physical Activity Questionnaire (IPAQ) short form, was used to evaluate each participant’s level of physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…The present study did not identify at which age the female disadvantage arises since it was already present at age 55, suggesting it could be a physiological sex difference. However, there was no sex difference demonstrated in similar physical performance tests among healthy adults aged 20 to 39 years [5,31,32], except for handgrip strength [33]. This may point towards sex differences in (un)healthy aging or to a ceiling effect of these tests.…”
Section: Discussionmentioning
confidence: 99%
“…The present study did not identify at which age the female disadvantage arises since it was already present at age 55, suggesting it could be a physiological sex difference. However, there was no sex difference demonstrated in similar physical performance tests among healthy adults aged 20 to 39 years [5,31,32], except for handgrip strength [33]. This may point towards sex differences in (un)healthy aging or to a ceiling effect of these tests.…”
Section: Discussionmentioning
confidence: 99%
“…No gender differences were found in this study. Torres et al found a weak balance in sedentary men and no differences between sexes in physically active adults [36]. Height was the only anthropometrical measure that was correlated with BESS score in group 1.…”
Section: Discussionmentioning
confidence: 90%
“…In the study, 72 h of sleep deprivation was used in an endurance athlete, and it was proved that his mental and physical well-being did not deteriorate after sleep loss. Therefore, it would be worthwhile to investigate the gender differences using a specially designed study needed to clarify this issue, especially that the positive effect of exercise is noticeable in men compared to women [ 55 ].…”
Section: Discussionmentioning
confidence: 99%